Cover Image, Volume 527, Issue 2. Issue 2 (30th December 2018) - Norekian, Tigran P.; Moroz, Leonid L.
Abstract : The cover image is based on the Research Article Neuromuscular organization of the Ctenophore Pleurobrachia bachei by Tigran P. Norekian and Leonid L. Moroz, DOI: 10.1002/cne.24546 .